THE INFLUENCE OF PRICE DISCOUNT ON PURCHASE INTENTION OF ONLINE PRODUCTS DURING COVID19 PANDEMIC IN INDONESIA: THE MEDIATION ROLE OF TRUST - Subagio, Dyajeng Puteri Woro (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The COVID-19 pandemic has a significant impact on decreasing income and community activities, including shopping behavior. Many people have decided to use the online marketplace platform to shop for various needs. This study aims to investigate the direct and indirect relationships between variable price discounts, trust, and purchase intentions for consumers of the most popular online marketplace platforms in Indonesia during the COVID-19 pandemic. In this study, the collecting data using an online questionnaire to 120 respondents as a sample who have met the purposive sampling criteria. This study uses Partial Least Square (PLS) to analyze the data. There is a uniqueness in this study where the price discount strategy cannot directly influence consumer purchase intention even though the economic condition has decreased due to the pandemic. This strategy encourages consumers to seek information about the products before making a purchase. The information of the products increases customer trust and purchase intention. It makes trust can fully mediate the relationship between the price discount strategy and purchase intention.